Nutrient removal using common reed (phragmites karka) and tube sedge (lepironia articulata) in a constructed surface flow wetland system in Putrajaya, Malaysia - Sim, Cheng Hua (2007)
A pilot tank study was carried out to determine the nutrient removal efficiency of the common reed Phragmites karka and tube sedge Lepironia articulata. The replicate planted tanks were continuously fed with a nutrient solution at a rate of 50.0 mg l-1 N and 5.0 mg l-1 P and control planted tanks were set up without nutrient supplements. The plant growth rate, plant nutrient removal efficiency and nutrient content in the substrate were analysed. In addition, a field study at the 3 wetland cells Upper North 4-6 in Putrajaya Wetlands was carried out to assess the plant nutrient removal efficiency and the nutrient removal rates along the 3 wetland cells. In the pilot study, the growth rate and total harvested biomass of treated wetland plants were significantly higher than of those in the control tanks. The treated samples of the common reed experienced a long growth period before they experienced senescence. However no flowering stage was observed throughout the 30-week experimental period. The treated tube sedge stands collapsed after 8 weeks in the first experimental period, probably due to nutrient overload conditions. In the second experimental period, the plant collapsed after 16 weeks under half nutrient concentration. Nutrient removal through nutrient accumulation by the common reed was higher than those in tube sedge at 42.12% N; 28.92% P and 17.43% N; 26.08% P respectively, and the differences were significant. The field study in Putrajaya Wetlands showed that water quality normally improved with flow length along the wetland cells. However the improvement is reduced during periods of rainfall where levels of Total Suspended Solids, Nitrate and Phosphate were highly variable. Nutrient removal performance was 82.11% Total Nitrogen (70.74% Nitrate-Nitrogen); and 84.32% Phosphate from UN 6 to UN 1 (2025 m) from April to December 2004. Both the pilot and field studies indicated that these two selected wetland plants grew well in the field and in the pilot tank study. Thus, both plant species are good examples of emergent plant species for constructed wetlands.